Survey-based investigations quality: guidelines for good reports - Mattos-Vela, Manuel Antonio (2020)
Studies quality evaluation is very important in the different scientific disciplines. Survey-based studies as well as other study types require high quality standards both in their execution and in their report, however, there is evidence indicating that it is not so. Many tools have been proposed to help assessing the survey-based reports quality, the vast majority neither are validated nor have a general consensus for their use; Therefore, the aim of this scientific note is to present the most accepted guidelines (SURGE and CHERRIES) that help inform this type of studies in an effective and transparent way.